2012
DOI: 10.1158/1535-7163.mct-11-1015
|View full text |Cite
|
Sign up to set email alerts
|

MiR-196a Is Upregulated in Gastric Cancer and Promotes Cell Proliferation by Downregulating p27kip1

Abstract: Aberrant expression of miR-196a has been frequently reported in cancer studies. However, the expression and mechanism of its function in gastric cancer remains unclear. Quantitative real-time PCR was carried out to detect the relative expression of miR-196a in gastric cancer cell lines and tissues. SGC7901 cells were treated with miR-196a inhibitors, mimics, or pCDNA/miR-196a to investigate the role of miR-196a in cell proliferation. Higher expression of miR-196a in gastric cancer tissues was associated with t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
87
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(98 citation statements)
references
References 34 publications
10
87
0
Order By: Relevance
“…In another study (Sun et al, 2012), higher expression of miR-196a in gastric cancer tissues was reported associated with tumor size, higher clinical stage, and shorter overall survival, and downregulation of miR-196a expression significantly suppressed the cellcycle progression, proliferation, and colony formation of gastric cancer cells in vitro, and ectopic miR-196a expression significantly enhanced the development of tumors in nude mice. Result of our study is partly consistent with these studies.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…In another study (Sun et al, 2012), higher expression of miR-196a in gastric cancer tissues was reported associated with tumor size, higher clinical stage, and shorter overall survival, and downregulation of miR-196a expression significantly suppressed the cellcycle progression, proliferation, and colony formation of gastric cancer cells in vitro, and ectopic miR-196a expression significantly enhanced the development of tumors in nude mice. Result of our study is partly consistent with these studies.…”
Section: Discussionmentioning
confidence: 91%
“…In previous study, mir-196a-5p was discovered over expressed in gastric cancer cell lines and gastric cancer tissues (Sun et al, 2012;Tsai et al, 2014). But the clinical significance of mir-196a-5p in cancers of previous reports was different, probably, which may be caused by different representatives of different samples.…”
Section: Introductionmentioning
confidence: 93%
“…More specifically, miR-193b was notably down-regulated in endometrioid adenocarcinoma, melanoma (Chen et al, 2010), hepatocellular carcinoma cells (Xu et al, 2010), and non-small cell lung cancer (NSCLC) (Hu et al, 2012), suggesting that miR-193b may act as a tumor suppressor and play a protective role in the carcinogenesis of these cancers. miR-196a is a known onco-miRNA that plays an important role in tumorigenesis and tumor progression (Peng et al, 2010;Sun et al, 2012). Emerging evidence suggests the aberrant over-expression of miR-196a is a frequent event in various cancers, including head and neck squamous cell carcinomas (Severino et al, 2013), laryngeal cancer (Saito et al, 2013), pancreatic cancer (Liu et al, 2013), and gastric cancer (Tsai et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, increasing evidence has demonstrated that miRNAs may be associated with lung cancer. A previous study revealed that an increase in hsa-miR-196a expression levels was a characteristic molecular change in NSCLC (8,9), and that hsa-miRNA-196a promoted NSCLC cell proliferation and invasion via targeting HOXA5 (10). Overexpression of miR-200 was shown to reduce the expression levels of NSCLC prognostic biomarkers in H1299 and BEAS-2B cells (11).…”
Section: Introductionmentioning
confidence: 94%